Prostate Cancer Metastatic to the Cervical Lymph Nodes - Luis Sepúlveda; Tiago Gorgal; Vanessa Pires; Filipe Rodrigues (Case Reports in Urology)
Prostate cancer is the most common cancer in men, often presenting with regional lymph node or bone metastasis and rarely with supradiaphragmatic lymph node involvement. Most metastatic cancers involving the cervical lymph nodes are from cancers of the upper aerodigestive tract. In this report, we describe two cases with cervical lymph node enlargement due to metastatic prostate cancer as the initial clinical presentation: a 43-year-old male, initially misdiagnosed with a tumor of the upper aerodigestive tract and an 87-year-old male with right lobe pneumonia and cervical lymph node enlargement, initially attributed to be an acute inflammatory lymph node reaction. To the best of our knowledge, there are less than 50 cases reported in the literature of adenocarcinoma of prostate metastatic to the cervical lymph nodes and only one case presenting in men younger than 45 years. The authors intend to highlight the importance of digital rectal exam and PSA test in case of persistent left cervical lymph node enlargement, including men younger than 45 years of age.